The sicilian inheritance eaudiobook A novel. - Piazza, Jo (Books on Tape, 2024)
NATIONAL BESTSELLER One of the NY Post's Best Beach Reads, an US Weekly pick for "mystery novels to read on the beach”, a Woman's World " captivating beach read you won't be able to put down this summer" ("a riveting saga"), an Eater food-filled beach read for your summer vacation ("an appealing mix of romantic escapism, whodunit intrigue, and feminist introspection.") From bestselling author and award-winning journalist Jo Piazza, comes "A Journey to the Boot of Italy, With Murder, Romance and Ricotta” ( The New York Times) about a disputed inheritance and a family secret that some will kill to protect . . . Sara Marsala barely knows who she is anymore after the failure of her business and marriage. On top of that, her beloved great-aunt Rosie passes away, leaving Sara bereft with grief. But Aunt Rosie’s death also opens an escape from her life and a window into the past by way of a plane ticket to Sicily, a deed to a possibly valuable plot of land, and a bombshell family secret. Rosie believes Sara’s great-grandmother Serafina, the family matriarch who was left behind while her husband worked in America, didn’t die of illness as family lore has it . . . she was murdered. Thus begins a twist-filled adventure that takes Sara all over the picturesque Italian countryside as she races to solve a mystery and learn the story of Serafina—a feisty and headstrong young woman in the early 1900s thrust into motherhood in her teens, who fought for a better life not just for herself but for all the women of her small village. Unsurprisingly the more she challenges the status quo, the more she finds herself in danger. As Sara discovers more about Serafina, she also realizes she is coming head-to-head with the same menacing forces that took down her great-grandmother. At once an immersive multigenerational mystery and an ode to the undaunted heroism of everyday women, The Sicilian Inheritance is an atmospheric, page-turning delight.